A qualitative exploration of speech-language pathologists' intervention and intensity provision for children with phonological impairment. (4th March 2021) - Hegarty, Natalie; Titterington, Jill; Taggart, Laurence
Abstract: Purpose: The aim of this study was to explore the reasons behind speech-language pathologists' (SLPs') current clinical practices (intervention and intensity provision) for children (0–18 years) with phonological impairment. Method: Three focus groups each with five SLPs and six 1:1 interviews with SLP managers from one region of the UK ( n  = 21) were carried out. A thematic analysis was undertaken. Result: SLPs often used an eclectic mix of familiar approaches with easily-accessible therapy materials. SLPs only reported deviating from their core approach if the child did not progress in therapy. Mixed responses were gathered on the perceived feasibility of transferring evidence-based intervention intensities into clinical practice. The importance of parents to increase intensity provision at home was noted. Barriers to SLPs' evidence-based decision-making included: time; confidence levels; service-related restrictions and; difficulty replicating research in practice. Having peer support and access to decision-making pathways and manualised intervention protocols were considered ways to overcome these barriers. Conclusion: There is a research-practice gap in which SLPs' current practices are driven by organisational factors, their own preferences and child-specific factors. To narrow this gap, SLPs suggested the development of time-saving, evidence-based tools.